Factores que inciden en la prevalencia de neumonía en niños menores de 1 año que acuden al servicio de pediatría del Hospital José María Velasco Ibarra De Tena. Año 2015 - Yauripoma Suqui, Dina Natalia (2016)
This research deals with factors affecting the prevalence of pneumonia in children under 1 year, who were admitted to the Pediatric Hospital José María Velasco Ibarra of Tena in 2015, data were collected using the techniques of direct observation technique, Data were collected through medical records and surveys of mothers, the study population was 59 children under 1 year. The research design was transverse, descriptive, bibliographic and field. As results were obtained for children 9-12 months reported higher percentage of pneumonia with 42.37%, male with 62.71%, 67.80% indigenous ethnic group, they come mostly from rural areas with 64.41%. The prevalence of pneumonia in children is 38.82%. Repeated respiratory infections 55.93%, the strong drafts 45.76%, Acute respiratory infection presence of relatives with 66,10%, poor hygiene at home 74.57%, overcrowding 62 is identified as the main risk factors , 71% and failure to attend medical controls 47.46%. It was concluded the main predisposing factors were: lack of hygiene at home, presence of relatives with Acute respiratory infection and the overcrowding. The author conducted educational activities through lectures and workshops at the hospital in Tena, at the health sub-center from community of Muyuna Talag.Keywords: Prevalence, Pneumonia, Children under 1 year Pediatric Service